A bi-directional drive model for lost motion behavior of planetary gear train. (August 2022) - Zhang, Chu; Dong, Huimin; Dong, Bo; Wang, Delun
Highlights: Propose a new bi-directional drive model for analyzing lost motion behavior of PGT. Reveal generation and abatement behavior of lost motion with multiple planet gears. Derive generalized formula of lost motion for different input components and errors. Suggest a reduction strategy of lost motion by analyzing eccentricity phase effect. Abstract: Lost motion is a key accuracy index of precision bi-directional gear drive. For planetary gear train (PGT), lost motion behavior is complex due to the coupling effects of multi-planet gears. In this paper, a new bi-directional drive (BDD) model of PGT is proposed considering the coupling effects of multi-planet gears and errors. With the BDD model, the generation mechanism and abatement behavior of lost motion with multi-planet gears are revealed, and a generalized formula of lost motion for PGT with different input components is derived from the lag in movement yielded by meshing clearance. The relationship between meshing clearance and manufacturing errors is determined by the vector loop equations. The effects of errors and manufacturing accuracy on lost motion behavior are analyzed. The eccentricity phase of planet gears on lost motion behavior is investigated through deterministic and statistical analysis, and a strategy of in-phase eccentricity arrangement is suggested for reducing the maximum lost motion. The lost motion test of an actual PGT is conducted. The results well agree with the simulations', which validates the proposed BDD model and reduction strategy.